Anemia and Pregnancy Interval in Relation to Childbirth Complications: Anemia dan Jarak Kehamilan dalam Kaitannya dengan Komplikasi Persalinan - Aida Navia; Siti Cholifah (Academia Open, 2023)
General Background: Childbirth complications threaten maternal and fetal health, particularly in cases of anemia and short pregnancy intervals. Specific Background: Complications at BPM Sri Sukarti Wlingi were high (33.3%) in August 2020. Knowledge Gap: Limited research exists on the impact of anemia and pregnancy intervals on childbirth complications. Aims: This study aimed to describe how pregnancy intervals and anemia relate to childbirth complications at BPM Sri Sukarti Wlingi. Results: A descriptive study with 30 samples found 80% of mothers had a safe pregnancy interval, and none were anemic. Complications were rare, with 87% of mothers experiencing none. High-risk pregnancy intervals showed 83.3% without complications. Non-anemic mothers were more likely to avoid complications (85.2%). Novelty: Risky pregnancy intervals and anemia were not major predictors of complications. Implications: Effective anemia management and regular prenatal care reduce complications, even in high-risk pregnancy cases. Highlights: Pregnancy Interval: 80% of mothers had a safe pregnancy interval, reducing complication risks. Anemia: None of the mothers experienced anemia, which contributed to fewer complications. Complications: 87% of mothers did not face complications, showing effective prenatal care management. Keywords: Anemia, Complications of Childbirth, Pregnancy Distance